Eco-Digital Trends: Consumer Behavior and Marketing Practices in the Dynamic Context of Global Warming - Fazel, Hesham (Journal of Economics and Administrative Sciences, 2024)
Purpose: This study targets climate change awareness of 4.54 billion internet users or 56% of the world’s population. It examines the reception of brand messages that bring out the aspects of ecological sustainability in the context of the cultural values of social media users. Theoretical framework: The positive link between consumer behavior and environmental responsibility was derived from a web-based survey and PLS-SEM analysis with 480 participants. Design/methodology/approach: The data obtained from the survey on 480 participants is evaluated through a web-based survey and PLS-SEM model that generates the digital platform’s interlinkage of consumer behavior with climate change awareness. Findings: This research depicts a positive association between consumer behavior and buying green, challenging the established notions of green consumerism. Research, Practical & Social implications: The findings call for redesigning green consumerism in the age of digitization and underpin future research on AI-driven green marketing. Originality/ value: This study provides in-depth new insights into the role of digital consumer behavior in promoting sustainability and identifies future research directions as we approach 2030-2050.